Identify Critical Success Factors (CSFs) for Sustainable Lean Manufacturing implementation in Indonesia Automotive Industry - Firdaus, Muhammad Fariz; Zagloel, Teuku Yuri M. (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The Indonesian automotive industry, known for its extensive supply chain and high resource consumption, demands operational strategies that promote both efficiency and sustainability. This study explores Sustainable Lean Manufacturing (SLM) as a strategic framework by identifying and prioritizing the Critical Success Factors (CSFs) necessary for its effective implementation. Using a mixed-method approach, the research applied the Delphi technique to gather expert consensus and the Analytical Hierarchy Process (AHP) to rank the identified CSFs. Data were collected through three rounds involving expert panels from various automotive firms with over a decade of experience in lean and sustainability practices. Nineteen CSFs were identified and grouped into six dimensions: Management and Leadership, Human Resources Development, Sustainable Production Process, Environmental Management, Supply Chain Management, and Safety and Well-being. Results show that Management and Leadership is the most influential dimension (51%), with Top Management Commitment ranked as the top CSF (0.2740). The study's methodological novelty lies in combining Delphi and AHP for sector-specific validation, filling the research gap on SLM in Indonesia’s automotive industry. The findings offer a structured decision-making model for practitioners to implement SLM initiatives that align with both operational goals and sustainability regulations. Future research is encouraged to apply this model to other industries and adopt AI-based tools for adaptive strategy development.